Measurement and modelling of young concrete properties - Fjellström, Peter (Luleå tekniska universitet, Byggkonstruktion och -produktion, 2013)
The main aim of this thesis is to refine models for strength and heat development of the young concrete, and evaluate if developed models at Luleå University of Technology (LTU) for creep, autogenous shrinkage and thermal dilation needs refinement. These are of importance in hardening control and in crack control of a concrete structure.Strength development is one of the most important properties in concrete to consider when analysing concrete structures. The need of actions on site is different at various stages of hardening, from the fresh concrete to the hardened concrete. This thesis defines a model analysing maturity and associated strength growth within three important time periods. The model can be applied separately within each of these periods depending on test data available. Known is that the temperature plays an important role on the strength development of concrete structures. Not so well known is that, if the concrete temperature remains high, strength reduction at later ages often occurs compared to hardening at lower temperature. Both these phenomena have been implemented in the model for strength growth and the functionality of the model is demonstrated by evaluation of laboratory tests for five concrete mixes and two types of cement.As heat of hydration affects the temperature levels and several other properties of concrete structures it is important to document the parameters accurately. In the traditional semi-adiabat (TSA) the measured heat energy originates from the reaction between cement and water. This energy warms up the concrete sample and all the ambient materials of the equipment. In order to model these energies, the TSA setup is transformed into an associated sphere. A refined model using a correction factor is introduced, which accounts for energies lost to the TSA setup materials. Results show that the effect of this factor cannot be disregarded. An increased insulation amount gives a decreased cooling factor but an increased need for correction.Creep at constant temperature, ...